Asparaginase Therapy in Pediatric Acute Lymphoblastic Leukemia: A Focus on the Mode of Drug Resistance - Shih-Hsiang Chen (Elsevier, 2015)
Asparaginase is one of the most important chemotherapeutic agents against pediatric acute lymphoblastic leukemia (ALL), the most common form of childhood cancer. The therapeutic efficacy (e.g., chemoresistance) and adverse effects of asparaginase (e.g., hypersensivity and pancreatitis) have been investigated over the past four decades. It was suggested early on that leukemic cells are resistant to asparaginase because of their increased asparagine synthetase activity. Afterward, other mechanisms associated with asparaginase resistance were reported. Not only leukemic cells but also patients themselves may play a role in causing asparaginase resistance, which has been associated with unfavorable outcome in children with ALL. This article will briefly review asparaginase therapy in children with ALL and comprehensively analyze recent reports on the potential mechanisms of asparaginase resistance.